Circulating MicroRNAs in the Second Trimester From Pregnant Women Who Subsequently Developed Preeclampsia: Potential Candidates as Predictive Biomarkers and Pathway Analysis for Target Genes of miR-204-5p - Luizon, Marcelo R.; Conceição, Izabela M. C. A.; Viana-Mattioli, Sarah; Caldeira-Dias, Mayara; Cavalli, Ricardo C.; Sandrim, Valeria C. (Frontiers in Physiology, 2021)
miRNAs play a role in pathophysiology of preeclampsia (PE). However, the expression of circulating miRNAs was not analyzed in the second trimester of pregnancy, a period of major relevance to identify predictive biomarkers for PE. Therefore, we examined the expression profiles of 84 circulating miRNAs using PCR-array in plasma collected between 20-25 weeks of gestation from pregnant women who subsequently developed PE and those who remained healthy along pregnancy randomly selected from a prospective cohort. Overall, 23 miRNAs had a fold change > 2.0 and were considered to be upregulated in plasma from pregnant women who subsequently developed PE, even before the onset of clinical symptoms of PE. However, only miR-204-5p was statistically significant (P-value = 0.0082). Experimentally validated interactions for target genes of miR-204-5p extracted from miRTarBase were used in gene set functional enrichment analysis to identify Reactome pathways. The network connecting the 37 target genes for miR-204-5p revealed pathways of known pathophysiological relevance during the early development of PE and include key genes related to PE, such as BDNF, MMP-9, MALAT1, TGFBR2, and SIRT1. We further depicted downstream targets of SIRT1 that are related to vascular endothelial function or implicated in the pathophysiology of PE, namely FOXO1, NFKB, HIF-1α, NOS3 and PPAR-y. Our novel findings provide for circulating miRNAs upregulated in the second trimester on plasma from pregnant women who subsequently developed PE that are potentially related to the early development of PE, which may guide further studies focused on the validation of potential predictive biomarkers in PE.